Sosialisasi UMKM Pelatihan Kewirausahaan Pembuatan Kemasan Produk Dan Persyaratan Halal Keamanan Produk - Yohanes Jhony Kurniawan; Heppy Julianto; Suhartono Suhartono (CV. Ulil Albab Corp, 2026)
This community service program took place at a micro-enterprise in RT 15 RW 7 Kampung Baru, Rawasari, Pulogadung, East Jakarta, which still lacked halal packaging and certification. This activity involved outreach and entrepreneurial mentoring, drawing on the experiences of a micro-enterprise in creating attractive packaging and halal certification. The expected outcome of this activity was to encourage micro-enterprises to create attractive packaging and obtain halal certification for their products. The method used was to share examples of micro-enterprises that have begun creating attractive product packaging and their success in obtaining halal certification. The results included an increased understanding of packaging, both as a product wrapper and a motivator for buyers to purchase the product. This also provided insight into the importance of halal certification and product certification from relevant units as a prerequisite for products to be marketed in modern retail.